EFFECTIVE READING FOR FOREIGN ENGLISH LANGUAGE LEARNER BY MAKING READING COMMUNICATIVE - Hurmaini, M. (Reflective, 2012)
Reading is an activity that is active and requires expertise and specific strategies that must be constantly socialized and developed for reading activities can be done with effective and efficiently. Reading comprehension in English especially related to how for a parson employed under a lot of vocabulary and is associated with a particular context so that the understanding in reading more leverage. Technique read the English text can be conducted by skimming and scanning. To face the test TOEFL is understanding of English reading, reader can conduct the trick: a) look for the detail information, b) find the sentence paraphrase, c) find the fact and opinion, d) indentify the discussion fundamental, e) chose best title.